1987
DOI: 10.1152/ajpcell.1987.253.6.c766
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 and tumor necrosis factor do not regulate protein balance in skeletal muscle

Abstract: Recent studies have claimed that interleukin 1-containing preparations increase skeletal protein degradation similar to that seen during infection and inflammation. However, preparations employed have contained other products of activated macrophages, including tumor necrosis factor-alpha. In the present report, we investigated the capability of recombinant-derived murine and human interleukins 1-alpha and 1-beta and human tumor necrosis factor-alpha to affect skeletal protein synthesis and degradation both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
58
1
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(69 citation statements)
references
References 22 publications
9
58
1
1
Order By: Relevance
“…In a recent study by Beck and Tisdale (1987) evidence was presented that a 'muscle tissue proteoteolytic factor' is produced by a murine adenocarcinoma of the colon called MAC 16, a tumour selected for its ability to induce severe cachexia in mice. Further evidence that polypeptide factors with similar biological activity are produced by activated macrophages is presented here (Table I) and elsewhere Goldberg et al, 1988;Moldawer et al, 1987).…”
Section: +26 -23supporting
confidence: 58%
See 2 more Smart Citations
“…In a recent study by Beck and Tisdale (1987) evidence was presented that a 'muscle tissue proteoteolytic factor' is produced by a murine adenocarcinoma of the colon called MAC 16, a tumour selected for its ability to induce severe cachexia in mice. Further evidence that polypeptide factors with similar biological activity are produced by activated macrophages is presented here (Table I) and elsewhere Goldberg et al, 1988;Moldawer et al, 1987).…”
Section: +26 -23supporting
confidence: 58%
“…This protein secreted by activated monocytes may be IL-1 or a IL-i-like peptide (Baracos et al, 1983;Dinarello et al, 1984). It has also been shown that prostaglandin E2 production was increased by these macrophage secretory products and an inhibitor of the cycloocygenase pathway, indomethacin, partially attenuated the stimulation in skeletal muscle protein degradation (Baracos et al, 1983 (Moldawer et al, 1987;Goldberg et al, 1988). Likewise, the involvement of TNF-a on catabolism of proteins has been demonstrated by some studies in vivo (Warren et al, 1987;Flores et al, 1989;Fong et al, 1989) and in vitro Charters & Grimble, 1989) and refuted in others (Kettelhutt & Goldberg, 1988;Moldawer et al, 1987;Rofe et al, 1987;Michie et al, 1988).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus the accelerated breakdown of protein appeared to be mediated by IL-1 in co-operation with other unidentified factors. However, Moldawer et al (1987) have shown that neither TNF-a or IL-1 regulate protein balance in skeletal muscle in vitro. Also in the present study the serum proteolysis-inducing factor is stable to heating at 60°C for 5 min suggesting that it is not a cytokine.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, acute in vivo administration of TNF-␣ has been shown to impair amino acid uptake by muscle (2,57). However, subsequent investigations generally failed to detect significant alterations in either the rate of protein synthesis or protein degradation in response to the acute injection of TNF-␣ (8,25,40,46). More recently, Zamir et al (58) was able to demonstrate a significant increase in proteolysis and a tendency for a decrease in protein synthesis in skeletal muscle incubated in vitro 2 h after a single injection of TNF-␣.…”
mentioning
confidence: 99%